If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + -26 = -20 + z Reorder the terms: -26 + 4z = -20 + z Solving -26 + 4z = -20 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -26 + 4z + -1z = -20 + z + -1z Combine like terms: 4z + -1z = 3z -26 + 3z = -20 + z + -1z Combine like terms: z + -1z = 0 -26 + 3z = -20 + 0 -26 + 3z = -20 Add '26' to each side of the equation. -26 + 26 + 3z = -20 + 26 Combine like terms: -26 + 26 = 0 0 + 3z = -20 + 26 3z = -20 + 26 Combine like terms: -20 + 26 = 6 3z = 6 Divide each side by '3'. z = 2 Simplifying z = 2
| 1.4Y=4.34 | | 750.00-500x=-185.00+35.00x | | 17=31c(c) | | 2x-6/2+3=10 | | 1.5(3x+2)-1.5x+4.5=15 | | x^2+9y^2-18x-18y+54=0 | | 44x^2-296=0 | | -4x+2(-6x-2)=-132 | | 5X-15=159 | | 2y=ax+6 | | -2x+7(-2x+5)=-93 | | -4(6m+4)= | | 24x^2-16x^3+8x^4= | | 1/5(5x03)4 | | 8(y-2)=6y-26 | | 8x-10=2(3+2x) | | 3x+6=-2(0.6-x) | | 5y+7=4 | | 4x^2(6-4x+2x^2)= | | 2/7(-35d) | | 2x+36/6 | | .25p+.5(1600-p)=.15(1600) | | y=9x-4 | | 8+x+x=1800000 | | 3(4x^2-6x^3+5x-7)-(4x^3-3x^2+11x+5)=0 | | y=3x-101 | | 11x+12=144 | | t/16=1600/40 | | 7x+3x=15+7x | | 3x-2=-3(1.5-x) | | -2-8=6+x | | 3x^8-2x^4-1=0 |